2011
DOI: 10.1186/1472-6963-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Perceived unfairness in working conditions: The case of public health services in Tanzania

Abstract: BackgroundThe focus on the determinants of the quality of health services in low-income countries is increasing. Health workers' motivation has emerged as a topic of substantial interest in this context. The main objective of this article is to explore health workers' experience of working conditions, linked to motivation to work. Working conditions have been pointed out as a key factor in ensuring a motivated and well performing staff. The empirical focus is on rural public health services in Tanzania. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 37 publications
5
65
1
2
Order By: Relevance
“…Spector points out that the correlation between pay and job satisfaction tends to be surprisingly small, which suggests that pay itself is not a strong factor in job satisfaction; however, pay fairness can be a very important factor [6]. Similarly, a study by Songstad et al of health workers in a rural district in Tanzania showed that unfairness in salary level, allocation of allowances, promotions, access to training, and upgrading reduced staff motivation, affecting their work performance [26]. The participants in the present study were concerned that people in the same job earned more money because they were involved in projects that were funded by international organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Spector points out that the correlation between pay and job satisfaction tends to be surprisingly small, which suggests that pay itself is not a strong factor in job satisfaction; however, pay fairness can be a very important factor [6]. Similarly, a study by Songstad et al of health workers in a rural district in Tanzania showed that unfairness in salary level, allocation of allowances, promotions, access to training, and upgrading reduced staff motivation, affecting their work performance [26]. The participants in the present study were concerned that people in the same job earned more money because they were involved in projects that were funded by international organizations.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, nurses can be differentiated into enrolled and registered nurses, with the latter undergoing longer training and having a higher level of qualification (20, 21). Other related and skilled cadres included MDs in general and mid-level cadres such as AMOs and COs.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have documented frontline workers' perceptions of unfair remuneration with agitations for better remuneration in Ghana . Songstad et al (2011) also noted the influence of policy and political developments on worker remuneration and perceptions of injustice in Tanzania.…”
Section: Perceived Distributive Injustice Related To Wider Health Secmentioning
confidence: 99%
“…Worker motivation can be defined as the degree of willingness of the worker to maintain efforts towards achieving organizational goals (Franco et al 2002;Kanfer 1999). Extrinsic motivation factors including contingent rewards such as salary, policy reforms and organisational factors, and intrinsic motivation factors that embody the individual's desire to perform the task for its own sake, which is selfgenerated and non-financial such as interpersonal factors, have been cited as influencing worker motivation in Africa including Ghana (Agyepong et al 2004;Andersen 2004;Ansong-Tornui et al 2007;Bosu et al 2007;Chen et al 2004;Mutale et al 2013;Prytherch et al 2012;Rowe et al 2005;Songstad et al 2011;Willis-Shattuck et al 2008;Witter et al 2007). Thus worker motivation is an important indicator of the quality and responsiveness of an organization towards its frontline health workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation